Interdisciplinary Approaches in The Field of Architecture: Biomimicry - Aytıs, Saadet; KARABETÇA, ALİYE RAHŞAN (My University, 2018)
It is not possible for professions and occupations to exist without supports of other disciplines. Being abstracted from interdisciplinary conceptions inhibits professions to continue their existence. These professions are also influenced by circumstances of modern world that are impossible to detach from interaction and communication. Increasing needs, developing technology, newly emerged criteria and many more reasons are pushing professions to penetrate; this general movement can be seen and/or required less in some professions and more in others. Professions that are at a very critical point about self-updating and modernizing, are also in a direct relation to human life and they get more affected by positive and negative conditions of the modern world. It is no longer possible for professionals to continue their professions without collaborating with other disciplines or benefit from their backgrounds. This type of collaboration always provides an interaction between disciplines. As a requirement of the information age, ways of accessing to information have increased and it became very easy to obtain information; these stimulate the interaction. Thus, professions become aware of and affect each other. In every part of life, everywhere that human life is in question, this situation becomes more specialized for architecture/interior architecture; it comes into prominence more than others. It is well known that every activity in life and professions which these activities are related create a common base in architecture. Development of an architectural project depends on projects, reports and technical data from different disciplines. Moreover, in some very special projects, it may become a must to get support from sociologists, psychologists, environmentalists, economists, etc. In this case, it becomes impossible to isolate contemporary architecture from other disciplines by evaluating it in an absolute formal way; this makes it impracticable to consider architecture in its own shell. Architecture/interior architecture that is fed by many other disciplines, also collaborate with biology substantially which helps architecture to gain biomimetic designs features. Biomimicry an interdisciplinary approach in many fields is fed by biology. This makes it possible to transfer biological designs into every discipline with a scientific approach where sustainable and resilient solutions are required. Biomimicry plays a very big role in bringing two unconnected terms together; technology and nature. Considering this role as an interdisciplinary approach in architecture puts a substantial contribution to the creation of sustainable designs. In this paper, biomimicry and collaboration of biology with architecture will be scrutinized in an interdisciplinary perspective.
Keywords: Architecture; biomimicry; interdisciplinary; biology; resiliency